Transformational Leadership and Creative Self-Efficacy on Educators’ Creativity: Can Innovation Climate be the Mediating? - Nailah Adiebah; Handrio Adhi Pradana (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2022)
The aim of this research is to examine the effect of Transformational Leadership, Creative-Self Efficacy, Innovation Climate, and Employee Creativity. Data from this study was obtained by distributing questionnaires to 301 educators who work in Formal Educational Institutions from Kindergarten to Higher Education levels spread across several cities in Indonesia. This study uses quantitative methods, namely multiple regression analysis and Baron and Kenny’s analysis technique processed by SPSS 21 software. The results showed that Transformational Leadership and Creative Self-Efficacy have a positive and significant effect on Employee Creativity and Innovation Climate. Innovation Climate was proved to partially mediate the relationship between Transformational Leadership, Creative Self-Efficacy, and Employee Creativity. Contributions to the development of the concepts of leadership, self-efficacy, and creativity as well as practical implications are described in the discussion section of this paper.